Análise dos efeitos da fotobiomodulação na viabilidade e características de celulas-tronco de câncer de linhagens celulares derivadas de carcinoma epidermóide de boca - Ibarra, Ana Melissa Ccopa (2019)
The oral squamous cell carcinoma (OSCC) have a subpopulation of cells, termed as cancer stem cells (CSC), responsible for tumor growth, metastasis and therapeutic resistance. OSCC treatment may promote the development of oral mucositis, characterized by an inflammation with severe symptomatology. Photobiomodulation (PBM) is a tool for treatment and prevention of oral mucositis, however, the use of PBM remains controversy as it could promote tumor progression by acting in neoplastic cells, including the CSC, that could be remained in the tissue after treatment. Thus, the aim of this study is to evaluate in vitro the cellular viability and CSC characteristics in cell lines derived from OSCC after PBM using the clonogenic and sphere formation assay as well as flow cytometry to investigate the expression of CD44 and ESA. This study results show that the cellular viability and cellular autophagy results vary in relation to the irradiation frequency, the groups exposed to a single irradiation presented tumoral progression, the LED1+3J/cm² group presented raise of cellular viability trough MTT and VN assays, as well reduction of arbritary autophagy units. However, the promotion was inhibited when the cells were exposed daily, where LED3+3J/cm² and LED3+6J/cm² groups did not promote the cellular viability. The 6J/cm² group presented a cellular viability reduction profile. No change in gene relationed to stem cell fenotype, epithelial mesenchymal transition and cellular differentiation was observed. No alteration in the cellular populations marked with CD44/ESA was observed. A reduction in sphere formation was observed for the LED3 groups. The parameters used for clinical practice were not capable of promoting the cellular viability of tumoral cell lines, nor favor the stem cell fenotype.